2018
DOI: 10.1016/j.bcp.2018.08.040
|View full text |Cite
|
Sign up to set email alerts
|

When orexins meet cannabinoids: Bidirectional functional interactions

Abstract: A growing body of evidence suggests the existence of biochemical and functional interactions between the endocannabinoid and orexin systems. Cannabinoid and orexin receptors have been shown to form heterodimers in agreement with the overlapping distribution of both receptors in several brain areas, and the activation of common intracellular signaling pathways, such as the MAP kinase cascade. The activation of orexin receptors induces the synthesis of the endocannabinoid 2-arachidonoyl glycerol suggesting that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 113 publications
0
27
0
Order By: Relevance
“…A direct role of eCBs has been proposed in the formation of episodic memory 5 , 34 whereas Cannabis consumption may interfere with the formation of new memories 35 . The biosynthesis of the eCB, 2-arachidonoylglycerol (2-AG) via diacylglycerol lipase α (DAGLα), and subsequently the signaling of CB1 receptors, are stimulated by OxA 36 , a neuropeptide produced by neurons in the lateral perifornical area of the hypothalamus (LH) and involved in the sleep/wake cycle, arousal, appetite, and energy homeostasis and acting via the G q/11 protein-coupled orexin receptor-1 (Ox1-R) and orexin receptor-2 37 , 38 . OxA is emerging as a regulator of neurogenesis and hippocampal plasticity 38 41 .…”
Section: Introductionmentioning
confidence: 99%
“…A direct role of eCBs has been proposed in the formation of episodic memory 5 , 34 whereas Cannabis consumption may interfere with the formation of new memories 35 . The biosynthesis of the eCB, 2-arachidonoylglycerol (2-AG) via diacylglycerol lipase α (DAGLα), and subsequently the signaling of CB1 receptors, are stimulated by OxA 36 , a neuropeptide produced by neurons in the lateral perifornical area of the hypothalamus (LH) and involved in the sleep/wake cycle, arousal, appetite, and energy homeostasis and acting via the G q/11 protein-coupled orexin receptor-1 (Ox1-R) and orexin receptor-2 37 , 38 . OxA is emerging as a regulator of neurogenesis and hippocampal plasticity 38 41 .…”
Section: Introductionmentioning
confidence: 99%
“…Several works support the idea that there is an interplay between cannabinoid and orexin systems, reviewed by Berrendero et al . ( 23 ) and Flores et al . ( 39 ).…”
Section: Discussionmentioning
confidence: 95%
“…The CB1R and OX2R have presented an overlapping distribution area in some regions of the CNS, based on anatomical studies ( 20 21 22 ); thus could be said that they can mutually regulate several physiological functions such as reward, nociception, food intake and energy balance, as reviewed by Berrendero et al . ( 23 ). Moreover, bioluminescence energy transfer assay showed that both OX1R and OX2R are capable of forming homo- and heteromeric complexes with one another and with the CB1R ( 24 ).…”
Section: Introductionmentioning
confidence: 99%
“…In the brains of nd- fads2 −/− mice, the two novel endocannabinoids took over the function of AEA and 2-AG in the retrograde action as ligands of presynaptic CB1 on orexinergic neurons in different areas of brain (lateral hypothalamus, hippocampus, arcuate nucleus. The release of inhibitory GABAergic inputs promotes increased appetite and feeding and increased body fat mass, resulting in obesity, and excitatory glutamatergic inputs, suppressing hunger and induce hypophagy (14, 35, 36).…”
Section: Discussionmentioning
confidence: 99%